Impact of model‐based science curriculum and instruction on elementary students' explanations for the hydrosphere. Issue 5 (10th October 2018) - Baumfalk, Ben; Bhattacharya, Devarati; Vo, Tina; Forbes, Cory; Zangori, Laura; Schwarz, Christina
Abstract: Developing scientific literacy about water systems is critical for K‐12 students. However, even with opportunities to build knowledge about the hydrosphere in elementary classrooms, early learners may struggle to understand the water cycle (Forbes et al., 2015 ; Gunckel et al., 2012 ; Zangori et al., 2015 ; Zangori et al., 2017 ). Scientific modeling affords opportunities for students to develop representations, make their ideas visible, and generate model‐based explanations for complex natural systems like the water cycle. This study describes a comprehensive evaluation of a 5‐year, design‐based research project focused on the development, implementation, revision, and testing of an enhanced, model‐centered version of the Full Option Science System (FOSS) Water (2005) unit in third grade classrooms. Here, we build upon our previous work (Forbes et al., 2015 a; b; Vo et al., 2015 ; Zangori et al., 2015 ; Zangori et al., 2017 ) by conducting a comparative analysis of student outcomes in two sets of classrooms: (1) one implementing the modeling‐enhanced version of the FOSS Water unit developed by the research team ( n = 6), and 2) another using the standard, unmodified version of the same curricular unit ( n = 5). Results demonstrate that teachers in both conditions implemented the two versions of the curriculum with relative fidelity. On average, students exposed to the modeling‐enhanced version of the curriculum showed greater gains in their model‐based explanations for the hydrosphere. Engagement in scientific modeling allowed students to articulate hydrologic phenomena by (1) identifying various elements that constitute the hydrosphere, (2) describing how these elements influenced the movement of water in the hydrosphere, and (3) demonstrating underlying processes that govern the movement of water in the hydrosphere.